Pelatihan Remaja Desa dalam Pemahaman Hukum Islam Menuju Generasi Islam Rahmatan Lil ‘Alamin - Muslimah, Hanifatim; Anam, Saeful (Community: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to improve children's understanding of Islamic law through demonstration as a practical and applicable learning approach. The background of this activity stems from the low ability of children to understand and practice worship in accordance with Islamic law, especially in aspects of fiqh such as wudhu, prayer, and tayamum. The method used is Service Learning (SL) with stages of planning, implementation, evaluation, and follow-up. In the planning stage, a Focus Group Discussion (FGD) was held with the community to identify needs and design an appropriate form of assistance. The activity was carried out every day (except Sunday) with a lecture, discussion, and demonstration approach so that participants were active, effective, and enthusiastic in learning. The results of the activities showed significant improvements in the cognitive, affective, and psychomotor aspects of the participants. Based on the evaluation data, the average score of the participants increased from 75.37 in the pre-test to 89.21 in the post-test. The children showed high motivation to learn, active participation, and improved practical worship skills. Full support from the community and parents reinforced the success of this program and encouraged the formation of a collective awareness of the importance of early Islamic legal education. This activity contributed significantly to building a knowledgeable, skilled, and Islamic-minded young generation. This success became the basis for developing similar programs on an ongoing basis and forming religious learning communities at the community level.